Thin films produced on 5052 aluminum alloy by plasma electrolytic oxydation with red mud-containing electrolytes - Sottovia, Livia [UNESP]; Pereira Antunes, Maria Lucia [UNESP]; Antonio, Cesar Augusto [UNESP]; Rangel, Elidiane Cipriano [UNESP]; Cruz, Nilson Cristino da [UNESP] (Univ Fed Sao Carlos, Dept Engenharia Materials, 2014)
In this paper, we propose the production of ceramic protective thin films by plasma electrolytic oxidation using red mud-containing electrolytes. The treatments were performed through the application of pulsed voltage (600 V, 200 Hz) during 300 seconds to aluminum samples immersed in electrolytic solutions with 5 g of red mud per liter of distilled water. The coatings were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), X-ray energy dispersive spectroscopy (EDS) and contact angle and surface energy measurements. The final current density during the experiments was 0.05 A/cm(2) and films as thick as 9.0 mu m have been obtained. XRD patterns have clearly shown the incorporation of species from the red mud on the coating.
Keywords: Plasma electrolytic oxidation; Ceramic coatings; Red mud